The Influence of Entrepreneurial Orientation, Governance, and Business Environment on Performance: Business Assistants as Moderator - Jeffry Martin Monang; Mokhamad Anwar; Sutisna (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
These cooperatives are a strategic Indonesian government initiative to strengthen the local economy. However, many still face challenges in governance, entrepreneurial capability, and adapting to a dynamic business environment. This study examines the influence of entrepreneurial orientation, cooperative governance, and the business environment on cooperative performance while investigating the moderating role of business assistants in Merah Putih Village/Subdistrict Cooperatives. This quantitative study used PLS-SEM to analyze data from 150 cooperatives using SmartPLS. The findings demonstrate that entrepreneurial orientation, cooperative governance, and the business environment each have a positive and significant effect on cooperative performance. Furthermore, business assistants significantly strengthen the relationship between entrepreneurial orientation and cooperative performance as well as the relationship between cooperative governance and cooperative performance. These findings indicate that effective mentoring enhances the capacity of cooperative managers to implement entrepreneurial practices, improve governance quality, and achieve better organizational performance. The study contributes to the cooperative management literature by extending the Resource-Based View, Social Exchange Theory, Human Capital Theory, and Contingency Theory through the integration of Business Assistants as a moderating variable. The findings also provide practical implications for policymakers in designing sustainable mentoring programs to improve cooperative performance.